PENGELOLAAN DAYA TARIK WISATA NGLANGGERAN PATUK GUNUNG KIDUL: PERSPEKTIF BIDANG HUKUM, EKONOMI, FILSAFAT - Nusanto, Tri Suyud; Nurmoko, Aditya Hera; yanti, aris indri; Primawati, Natalia Heni (PRIMA EKONOMIKA, 2023)
This study aims to analyze the management of tourist attractions in Nglanggeran, Patuk, Gunung Kidul, with a cross-faceted approach to law, economics, and philosophy. Although Nglanggeran has become a popular tourist destination, challenges in effective management of tourist attractions still need to be addressed. In reviewing legal aspects, this study will explore regulations and policies governing tourism management in Nglanggeran, including environmental protection, local community rights, and related permits and regulations. In the economic aspect of tourism, this study will analyze the economic contribution of tourism to local communities, the potential for sustainable economic development, and the economic benefits of the tourism sector. From a philosophical perspective, this study will review the values and principles underlying the management of tourist attractions in Nglanggeran, including ethical and sustainability concepts for the development and maintenance of sustainable tourist destinations. The research method used is a qualitative approach with data collection through field observation, interviews with relevant stakeholders, and document analysis related to tourism law, philosophy, and economics. It is hoped that the results of this study can provide a more comprehensive understanding of the governance of tourist attractions in Nglanggeran and recommendations for improvements in sustainable tourism management. Keywords: tourism attraction management, Nglanggeran, law, tourism economics philosophy